2023
DOI: 10.1101/2023.03.20.533550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmembrane Stem Factor Nanodiscs Enhanced Revascularization in a Hind Limb Ischemia Model in Diabetic, Hyperlipidemic Rabbits

Abstract: Therapies to revascularize ischemic tissue have long been a goal for the treatment of vascular disease and other disorders. Therapies using stem cell factor (SCF), also known as a c-Kit ligand, had great promise for treating ischemia for myocardial infarct and stroke, however clinical development for SCF was stopped due to toxic side effects including mast cell activation in patients. We recently developed a novel therapy using a transmembrane form of SCF (tmSCF) delivered in lipid nanodiscs. In previous studi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Takematsu et al [ 58 ] revealed, in their study, that the therapeutic potential effect of the transmembrane form of SCF (tmSCF) nanodiscs was a possible treatment option for peripheral ischemia. They treated rabbits with tmSCF nanodiscs, which were implemented into the ischemic limb of the rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takematsu et al [ 58 ] revealed, in their study, that the therapeutic potential effect of the transmembrane form of SCF (tmSCF) nanodiscs was a possible treatment option for peripheral ischemia. They treated rabbits with tmSCF nanodiscs, which were implemented into the ischemic limb of the rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, the histological analysis revealed a significantly elevated amount of large and small blood vessels in the ischemic muscles of the tmSCF nanodisc-treated group. Importantly, the researchers did not spot mast cell activation or inflammation in the rabbits [ 58 ]; see Table 15 .…”
Section: Discussionmentioning
confidence: 99%